ENGINEERING SMART GOVERNANCE SYSTEMS AND E-GOVERNMENT SERVICES FOR URBAN SUSTAINABILITY: A SYSTEMS-BASED APPROACH TO SDG-ALIGNED URBAN EFFICIENCY - Saba Bukhari; Shah Muhammad Kamran; Muhammad Asif; Muhammad Moinuddin Qazi Abro; Khalid Zaman (Spectrum of Engineering Sciences, 2025)
Smart cities, a crucial answer to urbanization's mounting difficulties, are transforming ecosystems worldwide. This study examines how smart infrastructure, digital connectivity, e-government services, renewable energy integration, and intelligent governance policies affect urban efficiency in Pakistan. Studying urban characteristics and identifying sustainable development solutions are crucial in light of the expansion of urbanization. The study employed a two-stage least squares (2SLS) regression technique, using quarterly data from 1996Q1 to 2022Q4. The results show that digital connection, e-government service adaptability, renewable energy integration, and quality of life enhance urban efficiency. Digital connectivity enables the effective management of urban processes, services, and infrastructure, making cities more livable, resilient, and ecologically friendly. Government online services improve management and empower citizens. Renewable energy helps cities become more resilient and solve environmental issues. Nevertheless, governments must collaborate to overcome structural impediments that may hinder these projects. Smart infrastructure, digital connectivity, e-government services, and renewable energy sources may help Pakistan achieve fair and sustainable urban development. Policymakers should support sustainable urban expansion to secure a prosperous future for future generations.